2004
DOI: 10.1091/mbc.e03-11-0788
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis as a Mechanism for Tyrosine Kinase-dependent Suppression of a Voltage-gated Potassium Channel

Abstract: The voltage-gated potassium channel Kv1.2 undergoes tyrosine phosphorylation-dependent suppression of its ionic current. However, little is known about the physical mechanism behind that process. We have found that the Kv1.2 alpha-subunit protein undergoes endocytosis in response to the same stimuli that evoke suppression of Kv1.2 ionic current. The process is tyrosine phosphorylation-dependent because the same tyrosine to phenylalanine mutation in the N-terminus of Kv1.2 that confers resistance to channel sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
105
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 71 publications
(78 reference statements)
5
105
0
Order By: Relevance
“…Kv1.2 currents are decreased upon Tyr kinase activation (22) through increased Kv1.2 endocytosis dependent on an intact Y132 residue in the Kv1.2 N terminus (23). As such, the Y132F mutant exhibits increased steady-state levels of Kv1.2 expression (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kv1.2 currents are decreased upon Tyr kinase activation (22) through increased Kv1.2 endocytosis dependent on an intact Y132 residue in the Kv1.2 N terminus (23). As such, the Y132F mutant exhibits increased steady-state levels of Kv1.2 expression (23).…”
Section: Discussionmentioning
confidence: 99%
“…Kv1.2 currents are decreased upon Tyr kinase activation (22) through increased Kv1.2 endocytosis dependent on an intact Y132 residue in the Kv1.2 N terminus (23). As such, the Y132F mutant exhibits increased steady-state levels of Kv1.2 expression (23). Phosphorylation at S440/S441 presumably acts through a distinct mechanism, because the S440A/S441A double mutation reduces cell-surface Kv1.2 expression of both WT Kv1.2 and the Y132F mutant to a similar extent (H.V.…”
Section: Discussionmentioning
confidence: 99%
“…HEK293 cells stably expressing Kv1.2, Kv␤2, and the M1 muscarinic acetylcholine receptor under Zeocin and G418 selection, respectively, were cultured as reported (2).…”
Section: Methodsmentioning
confidence: 99%
“…That evidence, along with mutagenesis studies, led to the hypothesis that cortactin was necessary for Kv1.2 function, and that its dissociation contributed to channel suppression. Subsequently, we found that the mechanism for channel suppression involves the dynamin-dependent endocytosis of Kv1.2 (2). That finding is particularly intriguing because cortactin's role in endocytosis is becoming increasingly apparent (3,4).…”
mentioning
confidence: 89%
“…Activation of muscarinic acetylcholine receptors, for example, elicits tyrosine phosphorylation of Kv1.2 and the resultant suppression of its ionic current (11). Tyrosine phosphorylation of Kv1.2 also elicits endocytosis of the channel, and this endocytosis is a mechanism for current suppression (10). This process is dependent upon the proteins dynamin and cortactin, both of which are well known for their roles in endocytosis (12)(13)(14).…”
mentioning
confidence: 99%